HUBUNGAN KARIES GIGI DAN PERILAKU MENYIKAT GIGI PADA SISWA KELAS V SDN 2 SEDANG ABIANSEMAL KABUPATEN BADUNG TAHUN 2016 - Ni Ketut Ratmini; I Gusti Ngurah Agung Darma Yuda (Jurnal Kesehatan Gigi (Dental Health Journal), 2017)
The degree of health of a person or community is influenced by four factors, namely: environment, behavior, heredity, and health services. The biggest problem faced by the population of Indonesia as well as in other developing countries in the field of dental and oral health is hard tooth tissue disease (caries dentis). The indicator of community dental maintenance behavior in maintaining oral health is the indicator of tooth brushing. Conclusions from the results of research I Gusti Ngurah Agung Darma Yuda on grade Vdi students of SDN 2 Moderate Badung Regency in 2016 that most students behaved wrongly in brushing their teeth and most students suffered dental caries. The purpose of this study was to determine the relationship of dental caries with tooth brushing behavior in fifth grade students of SDN 2, Badung Regency 2016. The type of cross sectional study used secondary data from I Gusti Ngurah Agung Darma Yuda's research. Spearmen correlation test between dental caries variables with tooth brushing behavior obtained sig values. 0.038. Conclusion there is a relationship between dental caries variables with tooth brushing behavior.